2019
DOI: 10.1016/j.ijpara.2019.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Ethylene Response Factor (ERF) genes modulate plant root exudate composition and the attraction of plant parasitic nematodes

Abstract: Plant root exudates are compositionally diverse, plastic and adaptive. Ethylene signalling influences the attraction of plant parasitic nematodes (PPNs), presumably through the modulation of root exudate composition. Understanding this pathway could lead to new sources of crop parasite resistance. Here we used Virus-Induced Gene Silencing (VIGS) to knock down the expression of two Ethylene Response Factor (ERF) genes, ERF-E2 and ERF-E3, in tomato. Root exudates were significantly more attractive to the PPNs Me… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…Genetic engineering of plants to enhance indirect defense has shown success in maize cultivar to enhance the constitutive production of ( E )-caryophyllene ( 21 ) to increase the recruitment of entomopathogenic nematodes . In plant–PPN interactions, the knockdown of ABC-C 6 transporter genes altered the root exudate composition and reduced the attraction of Meloidogyne and Globodera spp. , These studies show the potential application of crop improvement to develop cultivars that are resistant to economically important crop pests. Our findings suggest that masking the attractive signal, MeSA ( 16 ), with MeDiJA ( 28 ) could provide an avenue for interfering with host plant recognition by the nematodes.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Genetic engineering of plants to enhance indirect defense has shown success in maize cultivar to enhance the constitutive production of ( E )-caryophyllene ( 21 ) to increase the recruitment of entomopathogenic nematodes . In plant–PPN interactions, the knockdown of ABC-C 6 transporter genes altered the root exudate composition and reduced the attraction of Meloidogyne and Globodera spp. , These studies show the potential application of crop improvement to develop cultivars that are resistant to economically important crop pests. Our findings suggest that masking the attractive signal, MeSA ( 16 ), with MeDiJA ( 28 ) could provide an avenue for interfering with host plant recognition by the nematodes.…”
Section: Resultsmentioning
confidence: 99%
“…The detected compounds and their quantitative variations at the different time points of root infection are shown in Table 1. Statistical variation in the amounts released between the different time points of infection was evident for o-cymene (2), (E)-isolimonene (3), β-pinene (4), (+)-(2)-carene (5), αphellandrene (6), p-cymene (8), β-phellandrene (9), (E)-βocimene (11), nonanal (15), valencene (26), viridiflorene (27), and MeDiJA (28). Notably, we found a 2−7-fold increase in the amounts of (+)-(2)-carene (5) released in the root volatiles at 2-DPI and 7-DPI, respectively.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…240 Root exudates from ERF-E2 knockout tomato were significantly more attractive to PPNs Meloidogyne incognita and Globodera pallida. 241 The downstream factors of melatonin signal transduction pathway showed various functions in regulating plant biotic stress tolerance. High conservation of NACs from cereal crops in clade C indicated that their conservative function in suppression of fungal infection.…”
Section: Biotic Stressmentioning
confidence: 99%